2019
DOI: 10.15446/profile.v21n1.71378
|View full text |Cite
|
Sign up to set email alerts
|

Engaging English as a Foreign Language Students in Critical Literacy Practices: The Case of a Teacher at a Private University

Abstract: This paper describes the process English as a foreign language university students and their teacher underwent when engaging in critical literacy practices. Interviews, focus groups, questionnaires, students’ artifacts, and the teacher’s journal were used to collect data in this study. Findings suggest that when students engage in critical literacy practices, they are prone to reflect on the power they have as agents of social change, while developing language skills. However, teachers should be ready to encou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…Gómez Jiménez and Gutiérrez (2019) noted that the implementation of social media tools within an educational context contributes to the creation of an advantageous academic environment, turning EFL classrooms into peculiar spaces where "different linguistic and cultural worlds come into contact" (p. 94). Through this, students' linguistic and intercultural competences together with their media literacy skills are promoted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gómez Jiménez and Gutiérrez (2019) noted that the implementation of social media tools within an educational context contributes to the creation of an advantageous academic environment, turning EFL classrooms into peculiar spaces where "different linguistic and cultural worlds come into contact" (p. 94). Through this, students' linguistic and intercultural competences together with their media literacy skills are promoted.…”
Section: Discussionmentioning
confidence: 99%
“…A critical intercultural approach to teaching EFL has been implemented to develop the intercultural communication skills of students, and their critical thinking, social, and reflexive skills (Gómez Jiménez & Gutiérrez, 2019). The National Council of Teachers of English (NCTE) formulated the core components for media literacy necessary in the process of teaching EFL.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although there are many definitions of cr, there are few studies showing how it can be done at the undergraduate level. These studies focus mainly on the following: (a) the results of teaching cr in English reading comprehension courses for undergraduate students with varied proficiency levels (Giraldo, 2018;Haromi, 2014;Huang, 2011;Liu, 2017), (b) undergraduate students' responses to cr instruction in English courses (Esteban-Nuñez, 2014;Gómez-Jiménez & Gutierrez, 2019;Kuo, 2014), and (c) efl teachers' perceptions and difficulties when implementing cr (Belet & Dal, 2010;Gómez-Jiménez & Gutierrez, 2019;Rahimi & Askari-Bigdeli, 2015). They do not focus on the gains and challenges experienced by students with this pedagogy.…”
Section: Critical Readingmentioning
confidence: 99%
“…The few studies that have focused on these two issues have reported four main challenges: (a) inability to see authors' bias when stereotypes in texts apply to more than one social group (Giraldo, 2018), (b) problems to see textual organization as a tool for authors to position readers (Haromi, 2014), (c) difficulties to see stereotypes when these are rooted and tied to students' cultural identities (Gómez-Jiménez & Gutierrez, 2019), and (d) trouble to discuss political issues and challenge the status quo (Rahimi & Askari-Bigdeli, 2015).…”
Section: Critical Readingmentioning
confidence: 99%
See 1 more Smart Citation